2015
DOI: 10.1089/sur.2014.189
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Monomicrobial Necrotizing Soft Tissue Infections

Abstract: Background: Broad-spectrum antibiotic therapy is critical in the management of necrotizing soft tissue infections (NSTI) in the emergency setting. Clindamycin often is included empirically to cover monomicrobial gram-positive pathogens but probably is of little value for polymicrobial infections and is associated with significant side effects, including the induction of Clostridium difficile colitis. However, there have been no studies predicting monomicrobial infections prior to obtaining cultures. The purpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…They can be further divided by tissue layer, such as necrotizing fasciitis when involving fascia or myositis when involving muscle, or by anatomic location, such as Fournier gangrene when present in the genitalia and perineum [1][2][3][4]. These infections are polymicrobial up to 80% of the time, with a predominance of group A Streptococcus (GAS), Staphylococcus aureus, Enterococcus, and multiple anaerobic bacterial species [2,[5][6][7].…”
mentioning
confidence: 99%
“…They can be further divided by tissue layer, such as necrotizing fasciitis when involving fascia or myositis when involving muscle, or by anatomic location, such as Fournier gangrene when present in the genitalia and perineum [1][2][3][4]. These infections are polymicrobial up to 80% of the time, with a predominance of group A Streptococcus (GAS), Staphylococcus aureus, Enterococcus, and multiple anaerobic bacterial species [2,[5][6][7].…”
mentioning
confidence: 99%
“…Thus, prior investigations in NSTI have revealed a higher occurrence of monomicrobial infections, including GAS, in the upper extremities, while polymicrobial infections were more common in the truncal region (28). This study found a negative association between other surgeries performed last four weeks prior to the NSTI and GAS aetiology.…”
Section: Discussionmentioning
confidence: 97%
“…With more than 50% of patients presenting with septic shock, urgent and bactericidal intravenous antibiotics are recommended [11,12]. NSTIs are often polymicrobial, and although some admission characteristics have been correlated with monomicrobial forms [18,121,122], even the site of infection is insufficient to guide empiric antibiotic treatment [4,19,123,124]. This should cover both gram positive, gram-negative, and anaerobic bacteria, usually with a broad-spectrum β-lactam (e.g., piperacillin-tazobactam).…”
Section: Suggested Empiric Treatment For Suspected Nsti Based On Basic Microbiologymentioning
confidence: 99%